Brazilian economy in the 2000's: A tale of two recessions - Matheus Cardoso Leal; Márcio Issao Nakane (Latin American Journal of Central Banking (LAJCB), 2025)
During the 2008 Great Recession, the adoption of counter-cyclical economic policies made the Brazilian economy more resilient. However, a noteworthy shift occurred in 2014, marked by a deterioration in Brazil's macroeconomic landscape, primarily driven by a worsening debt situation. Consequently, this downturn led to a decline in private investment, an upswing in unemployment rates, and negative growth rates over multiple quarters. To comprehend these macroeconomic fluctuations, this paper employs the Business Cycle Accounting (BCA) analytical framework, focusing on quarterly data spanning from 2002 to 2019. Among the key findings, the study reveals that the efficiency wedge played a pivotal role in replicating observed output movements during both recessions, with the labor wedge following closely. Investment and government consumption wedges were not significant business cycle drivers in the period.
Keywords: E32; E65; 330; Brazilian recessions; Business cycle accounting